2019
DOI: 10.1007/s35834-019-00230-w
|View full text |Cite
|
Sign up to set email alerts
|

Unterstützendes Führungsverhalten schulischer Leitungskräfte für die Arbeit professioneller Lerngemeinschaften im Kollegium

Abstract: Zusammenfassung Ergänzend zu einer primär outcome-orientierten Erforschung von Professionellen Lerngemeinschaften wendet sich der Beitrag günstigen innerschulischen Entwicklungsbedingungen für die Arbeit dieser Gemeinschaften zu. Dabei interessiert vor allem, welche prädiktive Kraft unterstützende Führungspraktiken der Schulleitung für variierende Ausprägungen konstitutiver Merkmale von Professionellen Lerngemeinschaften besitzen und worin diese Führungspraktiken konkret bestehen. Um diesen Fragen nachzugehen,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 51 publications
0
6
0
5
Order By: Relevance
“…This is in line with findings from other studies showing a positive relationship between principal leadership and teacher collaboration (e.g., Goddard et al, 2015; Sehgal et al, 2017). To promote teacher collaboration, principals can create supportive structures in their schools, for instance, by providing regular opportunities for teachers to collaborate (Gray et al, 2016; Warwas et al, 2019). Apart from these structural prerequisites, however, teacher collaboration also depends on the quality of the social relations within a group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in line with findings from other studies showing a positive relationship between principal leadership and teacher collaboration (e.g., Goddard et al, 2015; Sehgal et al, 2017). To promote teacher collaboration, principals can create supportive structures in their schools, for instance, by providing regular opportunities for teachers to collaborate (Gray et al, 2016; Warwas et al, 2019). Apart from these structural prerequisites, however, teacher collaboration also depends on the quality of the social relations within a group.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to teacher collaboration, principals determine the overall conditions, for instance, by providing opportunities for teachers to work together with colleagues (Goddard et al, 2015; Gray et al, 2016). In addition, principals can promote teacher collaboration by creating a climate of mutual trust and involving teachers in decision-making processes (Warwas et al, 2019). Because studies have shown that teacher collaboration predicts good teaching practice and student achievement, principals should support their teachers in working together (e.g., Goddard et al, 2007; Moolenaar et al, 2012; Vescio et al, 2008).…”
Section: Principal Leadership and Teacher Collaborationmentioning
confidence: 99%
See 1 more Smart Citation
“…Biel et al 2018 Leonard 2001Leonard , 2003Holtappels 2020;Warwas und Schadt 2020). Dabei wird ein die PLG-und Bildungsarbeit unterstützendes Führungsverhalten als zentraler Einflussfaktor hervorgehoben (Warwas et al 2019). Für die WB nehmen wir an, dass zudem die organisationalen Rahmenbedingungen sowie die kooperationsbezogenen Überzeugungen der Lehrenden besonders relevant sind.…”
Section: Ausgangslage Und Entwicklung Der Fragestellungunclassified
“…So erweisen sich Kleingruppen vor allem zu Beginn der PLG-Implementierung als begünstigend (Buhren 2015). Zudem gelten klare Aufgabenverteilungen und Regeln, für alle transparente Arbeits-und Entscheidungsprozesse, handlungsbezogene, lehr-lernbezogene Ziele, eine relativ stabile Teambildung sowie ein Arbeitsklima, das von wechselseitigem Respekt und Vertrauen geprägt ist, als unterstützend (Bonsen et al 2013;Holtappels 2020;Roy und Hord 2006;Verbiest 2011;Warwas et al 2019).…”
unclassified